Entrepreneurship, a determinant factor in the sustainable development of small businesses - Manta P. Elena Otilia (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2019)
Entrepreneurship has emerged from people's permanent desire to meet their own needs, namely the permanent capacity to adapt to the new technological challenges of the markets and to create new elements to meet the needs of the market. Due to their innovative nature, entrepreneurs persist in discovering new sources of documentation to continually improve their activities. For the sustainable development of small businesses, especially in rural areas, the role of entrepreneurs is determined by their knowledge capacities in terms of supply, the cost of their products and services, and the mobilization of financial resources in the development of new businesses or the expansion of existing businesses.